The effectiveness of safe city programme in Taman Sungai Chua, Kajang, Selangor / Hannis Sabrina Zulkefle and Seng Boon Lim - Zulkefle, Hannis Sabrina; Seng, Boon Lim (2023)
Safe City Program was launched in Malaysia two decades ago. It aims to realize a safe living environment for city dwellers. However, little evidence is found to assess its effectiveness, and decision-makers lack evidence in furthering such urban policy. Taking the case study of Taman Sungai Chua, Kajang, Selangor, this study intends to fill in such a gap by assessing residents’ perception of the effectiveness of the safe city programme. The method used in this study is questionnaire surveys involving 122 respondents. The survey items largely related to the physical aspects of a residential area, i.e., built environment, and layout design. The collected data were analyzed through descriptive statistical analysis. The findings showed that the level of security in the Sungai Chua housing area as a place to live is at a moderate level. The gridiron layout design has influenced the occurrence of crime. Suggestions to sustain the safe city program in Taman Sungai Chua include building defensive boundaries, i.e., installing fences around the house, limiting the gridiron housing layout design – high level of access to restricted access; and increasing surveillance qualities, i.e., placing guard houses, installing closed-circuit television (CCTV) and lights for good lighting at night. This study has contributed a case evident in assessing the safe city programme in Malaysia. This finding would add insights for the decision-makers and residents in dealing with crime in residential areas.